Contingency in philosophy and history, 1650–1800. Issue 3 (16th March 2018) - Silver, Sean
ABSTRACT: This essay traces the history of a narrative and historiographic tension, of the inevitability that only appears after the fact. It offers a history of 'contingency', the modern affect that accompanies effects, the double-sensation of the inevitability of historical necessity with the knowledge that things might have been different. Tracing contingency through the literature and history of eighteenth-century Europe, it examines the historical development of one influential strategy whereby time turned up as an epistemological problem – and as a powerful technique leveraged by novelists and historians alike. Authors considered include John Dryden, Thomas Hobbes, Blaise Pascal, Adrien Richer, Frederick II, Horace Walpole, and Laurence Sterne.